“IMPROVING GRADE 6 LEARNING OUTCOMES USING LEARNING MEDIA INFORMATION SYSTEM (CASE STUDY OF KRISTEN PENABUR WACANA ELEMENTARY SCHOOL PURWOREJO)" - Victoria Angela Sugianto; Lasmedi Afuan; Nur Chasanah (Jurnal Teknik Informatika (Jutif), 2022)
The Covid-19 pandemic that has entered since March 2020, requires every sector to carry out all their activities online. One of them is in the field of education. SD Kristen Penabur Wacana is having difficulty providing additional classes or enrichment to grade 6 students. Due to the Covid-19 pandemic, students are learning online. Parents of grade 6 students admit that it is difficult to find additional material and teach it to their children. The school also does not have a learning system that can facilitate students in online learning. To overcome the existing problems, the researcher created an information system entitled “Sistem Informasi Media Pembelajaran Untuk Meningkatkan Hasil Pembelajaran Kelas 6 Sekolah Dasar (Studi Kasus SD Kristen Penabur Wacana Purworejo)”This system was created to make it easier for schools to provide additional classes or online enrichment. The development method used in this research is the Waterfall method. This system is built using the Codeigniter framework. Testing on this system shows that there are no failures in each module's functionality, so that this system is in accordance with user needs. With the information system built, it can make it easier for the school to provide additional classes or enrichment and to improve the learning outcomes of grade 6 students.